Mechanical characteristics of cotton fibre reinforced geopolymer composites - Alomayri, T.; Low, It-Meng (John Wiley & Sons., 2014)
This research is concerned with the mechanical properties of cotton fibre reinforced geopolymer composites (CFRGC). The effect of cotton fibre content on the flexural strength, the flexural modulus, the impact strength and the compressive strength were investigated. The density and porosity of cotton fibre reinforced geopolymer composites were also measured. The results indicate that cotton fibre content has a strong influence on the flexural strength, flexural modulus, impact strength and compressive strength of CFRGC. These cotton fibres reinforced geopolymer composites may be useful in civil engineering applications.